PARP inhibitors decrease response to subsequent platinum-based chemotherapy in patients with BRCA mutated ovarian cancer. Issue 10 (13th September 2021) - Rose, Peter G.; Yao, Meng; Chambers, Laura M.; Mahdi, Haider; DeBernardo, Robert; Michener, Chad M.; AlHilli, Miriam; Ricci, Stephanie; Vargas, Roberto
Abstract : To determine the effect of poly-adenosine ribose phosphatase inhibitors (PARPi) on the response to subsequent platinum-based chemotherapy (PBC) in patients with recurrent, platinum-sensitive BRCA -mutated epithelial ovarian, peritoneal, or fallopian cancer ( BRCA m EOC). This is a retrospective, single-institution cohort study of patients with BRCA m EOC who received retreatment with PBC. The PFS of patients with BRCA m EOC to 2nd or 3rd PBC with and without a prior PARPi was determined. Additionally, we compared the PFS to subsequent PBC following a prior PARPi for BRCAm and non-BRCAm. One hundred and fifteen patients with BRCA m EOC received a 2nd PBC and 55 received a 3rd PBC. The median PFS was 2.3 and 2.4 times longer, respectively for patients who did not receive a PARPi, (2nd P = 0.005, 3rd P < 0.001). Among 20 PARPi exposed patients with BRCA m EOC the PFS to a 2nd or 3rd PBC was worse at 8.0 months vs. 19.1 months HR 4.01 [2.25, 7.16], P < 0.001. Following PARPi exposure the PFS for patients with BRCA m EOC was similar for patients with platinum-free intervals of 6–12, 12–24 and >24 months. Following PARPi exposure the PFS was similar for patients with BRCA m EOC and non BRCA m EOC. Among patients with BRCA m EOC PARPi exposure significantly reduced PFS following 2nd and 3rd PBC. PARPi exposure nullifies established prognostic factors (i.e. platinum-free interval and BRCA mutational status) in platinum-sensitive recurrent ovarian cancer.